2013
DOI: 10.1021/jm400034b
|View full text |Cite
|
Sign up to set email alerts
|

Embellicines A and B: Absolute Configuration and NF-κB Transcriptional Inhibitory Activity

Abstract: Two new metabolites, embellicines A and B (1 and 2), were isolated from the EtOAc extract of the fungus Embellisia eureka , an endophyte of the Moroccan plant Cladanthus arabicus (Asteraceae). The structures of these new compounds were determined on the basis of extensive one- and two-dimensional NMR spectroscopy as well as by high-resolution mass spectrometry. The absolute configuration of embellicine A (1) was determined by TDDFT ECD calculations of solution conformers, whereas that of embellicine B (2) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 39 publications
4
44
0
Order By: Relevance
“…Pyrrocidine B ( 173 ) 156 and related compounds, such as hirsutellone B ( 172 ) 157 , GKK1032A 2 ( 174 ) 158 and embellicine A ( 175 ) 159 (Scheme 30A), are multicyclic hybrid PK-NRP compounds isolated from different fungal species with various biological activities. 160 These compounds share several common structural features: a fused 6-5-6 decahydrofluorene core, a 13-membered and strained paracyclophane, and a 5-hydroxypyrrolidinone moiety derived from reductive cyclization catalyzed by PKS-NRPS (see section 3.2).…”
Section: Radical Cyclization Mechanismsmentioning
confidence: 99%
“…Pyrrocidine B ( 173 ) 156 and related compounds, such as hirsutellone B ( 172 ) 157 , GKK1032A 2 ( 174 ) 158 and embellicine A ( 175 ) 159 (Scheme 30A), are multicyclic hybrid PK-NRP compounds isolated from different fungal species with various biological activities. 160 These compounds share several common structural features: a fused 6-5-6 decahydrofluorene core, a 13-membered and strained paracyclophane, and a 5-hydroxypyrrolidinone moiety derived from reductive cyclization catalyzed by PKS-NRPS (see section 3.2).…”
Section: Radical Cyclization Mechanismsmentioning
confidence: 99%
“…NRRL 46751 isolated from the lower crown of Saurauia scaberrinae (Actinidiaceae), 7 a plant growing in the central highlands of Papua New Guinea. Herein we report the isolation and characterization of three alkaloids, phomapyrrolidones A–C ( 1–3 ) bearing a rare cyclopenta[b]fluorene (6/5/6/5) ring system, 8 methylation of 1 to its N-methyl derivative 4 , and evaluation of 1–4 for their in vitro antitubercular and cytotoxic activity. Numerous secondary metabolites are known from endophytic strains of Phoma , 9 and our previous investigation of a culture broth of Phoma sp.…”
mentioning
confidence: 99%
“…The planar structure of 1 was deduced by analysis of its 1 H and 13 C NMR spectra (Table 1), 1 H– 1 H COSY and HMBC data (Figure 1), and comparison of these data with those reported for related fungal alkaloids. 8,1013 In its 1 H– 1 H COSY spectrum, 1 showed the presence of the spin systems CH 3 CH–, –CH 2 CHCH–, –CHCHCHCHCH(CH 3 )CH 2 CH(CH 3 )CH 2 CHCH–, and that due to a 1,4-disubstituted benzene ring. These data also suggested that 1 contained a succinimide moiety (δ c 171.6 and 177.3) and a tetracyclic cyclopenta[b]fluor-2(3),5(6)-diene ring system bearing six methyl groups at C–1, C–2, C–4, C–6, C–10, and C–12 and that the CH of CH 3 CH– spin system is a part of the tetracyclic ring (Figure 1).…”
mentioning
confidence: 99%
“…Tumor cell cytotoxicity and inhibitory effect on NF-κB transcriptional activity [210] Ilanepyrrolal (339)…”
Section: Cladanthus Arabicusmentioning
confidence: 99%
“…It was also observed that compound 338 was highly active due to its cytotoxic/cytostatic potential. Interestingly, compound 338 was 5-10 times more active than compound 337 against K562 cells, indicating that the hydroxylation pattern in the pyrrolidinone ring is more important for its cytotoxicity than the presence of a C17-C18 double bond [93]. …”
Section: Fig 82 (Continued)mentioning
confidence: 99%